Mitigating the Challenges and Capitalizing on Opportunities: A Qualitative Investigation of the Public Library's Response to an Aging Population. Issue 3 (26th September 2021) - Baluk, Kaitlin Wynia; Griffin, Meridith; Gillett, James
ABSTRACT: Public libraries are community hubs that can both create opportunities and address challenges often associated with later life and population aging. Using a thematic analysis of 18 in-depth interviews with public librarians, this study investigates common practices and challenges experienced while developing programs for older adults. This analysis is augmented by an environmental scan of older-adult programming offered in member libraries of the Canadian Urban Library Council (CULC). Results indicate that public librarians leverage community partnerships and staff training to develop programs that foster digital, financial, language, and health literacy and create opportunities for both intergenerational and peer social connection. At the same time, they face challenges related to limited space, budgets, and staff capacity, difficulty meeting the extensive and often conflicting interests of various groups within the library, and marketing programming to older adults. Findings indicate that public libraries may be key players in mitigating challenges often associated with having an aging population, and indeed highlight the many benefits of valuing and providing services to this population.